Eksistensi Etika Islam dalam Bingkai Moderasi Akhlak Berbasis Agama di Indonesia Perspektif Imam Ghazali - Fatahillah, Fatahillah; Mustopa, Mustopa; Hapidin, Ahmad; Ahyani, Hisam; Ahmad Zulfi Fahmi, (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2023)
The concept of ethics from Ghazali's perspective, especially regarding the existence of Islamic ethics, is based on good morals or noble character, so this concept needs to be applied in a pluralistic Indonesian society. Where in this case, within the frame of moderation of religion-based morality in Indonesia in the current era, the application of morality as offered by Ghazali is a must; this is because, in the concept of religious moderation in Indonesia, there are Islamic values that reflect good morals, namely in the form of attitude 1 ) tolerance, 2) non-violence, 3) acceptance of tradition, and 4) high national commitment. This research is a type of library research whose object of study uses library data in the form of books, journals, and other relevant sources of literature as the data source. Besides that, the researcher reads, reviews, and analyzes the existing literature to conclude. This research concludes that Ghazali's relevance regarding Islamic ethics in the framework of moderation of religion-based morality in Indonesia. The present era is relevant; this is proven by prioritizing Islamic ethics will manifest karimah (beginning) morals, then, in the end, will embody Islamic values rahmatan lil natural in all human activities.